Rehabilitation therapy for athletes after orthopedic surgery procedures on the forefoot - Staude, V.; Prozorovsky, D.; Radzyshevska, Y. (Journal of Physical Education and Sport, 2023)
Post-operative rehabilitation of patients is not less important, or even more important, than a technically perfect surgery procedure. A good functional result of treatment depends not only on surgery procedures, but also on an individually selected system of post-operative rehabilitation therapy, especially when it comes to athletes - patients with high functional requirements.